Personalidad y predicción - Avia, María Dolores (1980)
The author begins by explaining that the conflict among personality psychologist about permanency versus change -respectively identified with individual and situation- should not be such, given that people change and certain situations remain. She agrees with Bem and Allen, thinking that there is more consistency than the one situational theorists recognize and that the conflict consistency/variability is an unsound dichotomy placed by them between nomothetic and ideographic approaches, instead of between individual and situation. It is pointed out that Bem and Allens work offers solutions and opens up new research pathways. She also comments on Bem and Funders work stressing that it offers the possibility of a classification of different situations by means of showing the behaviour they tend to provoke in different individual types. This feasibility of this approach is tried out in three different experimental situations and the first one of them -in which the behaviour of children under delay of gratification circumstances is studied- is discussed by the author in relation to her own works. Finally, she reflects on the limits of the psychological discipline as able to precisely predict human behaviour.